Surgeon experience affects outcome of forearm arteriovenous fistulae more than outcomes of upper-arm fistulae - Regus, Susanne; Almási-Sperling, Veronika; Rother, Ulrich; Meyer, Alexander; Lang, Werner (Journal of Vascular Access, 2017)
There is still an ongoing discussion about the influence of vascular surgeon experience on the immediate and long-term outcome of newly created arteriovenous fistula (AVF) for patients on hemodialysis (HD). The aim of this study was to compare failure and patency rates of AVF between experienced consultants and resident trainees with special focus on location of the anastomosis on the forearm or upper arm.Between November 2012 and September 2016, 159 patients (83 on HD and 76 preemptive) received an AVF (90 radiocephalic [RCAVF] on the forearm; 69 brachiocephalic [BCAVF] in the elbow) by two experienced vascular surgeons (group A; n = 74) or five residents in training with one-to-four years of experience (group B; n = 85). We compared the two groups for demographic and treatment data, immediate failures (IF), bleeding complications and patency rates.There were no significant differences in demographic data between the two groups. Vessel diameters were significantly lower for forearm compared to upper arm arteries (p = 0.026) and veins (p = 0.05). There was a significantly increased risk for IF in group B for RCAVF (p = 0.003), but not for BCAVF (p = 1.000). Furthermore, the cumulative primary patency was reduced in group B for RCAVF (p<0.001), but not for BCAVF (p = 0.899).Surgeon experience seems to have more influence on the immediate and long-term outcome of newly created forearm AVF compared to those located on the upper arm.
EVALuna2:15320